The role of data and knowledge in firms' service and product innovation - Heli Koski (The Research Institute of the Finnish Economy (ETLA), 2012)
The importance of data and different sources of knowledge in the development of new services and products, and further in the creation of new markets, has dramatically increased during the past few decades. This empirical study uses data from 531 Finnish firms to explore the determinants of generation of new data-based products and services. The empirical findings emphasize the role of a firm's absorptive capacity and its ICT competence in data-based innovation. It seems that generally a firm's external information sources play a more prominent role than internal information sources. Particularly customer involvement in innovation process positively relates to the production of new data-based products and services. The reported empirical findings further indicate that data-based product and service innovation tends to be rather strongly demand-driven.
Keywords: D22; L20; O31; 330; firm performance; innovation; data-based products and services; ICT; Innovationsmanagement; Wissensmanagement; Informationstechnik; Unternehmenserfolg; Finnland